2018
DOI: 10.1093/rheumatology/key242
|View full text |Cite
|
Sign up to set email alerts
|

Management of major organ involvement of Behçet’s syndrome: a systematic review for update of the EULAR recommendations

Abstract: The majority of studies related to major organ involvement that informed the updated EULAR recommendations for the management of BS were observational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 104 publications
2
64
0
1
Order By: Relevance
“…Immunosuppressants demonstrated a decrease in recurrence of deep vein thrombosis while aminosalicylate drugs and azathioprine were found beneficial in gastrointestinal involvement. Immunosuppressants and glucocorticoids improved outcomes in nervous system involvement, and, relevant to this case, cyclophosphamide and high-dose glucocorticoids demonstrated decreased mortality in patients with PAP 9. Some cases of BD with pulmonary artery involvement require urgent intervention due to rapid enlargement or rupture of the PAP 10…”
Section: Discussionmentioning
confidence: 66%
“…Immunosuppressants demonstrated a decrease in recurrence of deep vein thrombosis while aminosalicylate drugs and azathioprine were found beneficial in gastrointestinal involvement. Immunosuppressants and glucocorticoids improved outcomes in nervous system involvement, and, relevant to this case, cyclophosphamide and high-dose glucocorticoids demonstrated decreased mortality in patients with PAP 9. Some cases of BD with pulmonary artery involvement require urgent intervention due to rapid enlargement or rupture of the PAP 10…”
Section: Discussionmentioning
confidence: 66%
“…In case of aneurysms of the aorta or in peripheral arteries, medical treatment with cyclophosphamide and corticosteroids is recommended as first choice, before considering operative repair [12]. The recurrence rate of DVT is significantly decreased when these patients are treated with immunosuppressives while anticoagulants did not reduce recurrence of DVT as shown in a meta-analysis of casecontrol studies [13]. If a patient also has extensive acute thrombosis, starting anticoagulation may be considered like in seven of our cases.…”
Section: Discussionmentioning
confidence: 75%
“…The use of anticoagulants and anti- fibrinolytic agents in BD is not currently recommended by EULAR [12]. As biologic treatments, mostly TNFinhibitors have become more important in the treatment of patients with BD, and further studies are needed to determine the place of biologics in HSS [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that due to its antiangiogenic activity, it also leads to reperfusion of occluded vessels and regression of neovascularization. 30 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 There is no standard usage. Some recommend starting at a high dose and then tapering after a response is achieved, while others prefer to start with a low dose and increase the dose according to the response achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The main adverse effects include the influenza-like symptoms experienced by nearly all patients, especially at the beginning of treatment, as well as alopecia, elevated liver enzymes, thyroiditis, autoantibody formation, weight loss, and depression. 21 , 97 The most important advantage of IFN-a-2a is that it can provide long-lasting remission that persists even after treatment is discontinued, and that the same effectiveness can be attained if treatment must be reinitiated. 95 , 96 …”
Section: Introductionmentioning
confidence: 99%